ANALISIS SEMIOTIKA PADA FILM DI KAMPUANG RASO MARANTAU KARYA IBEL SANTANO (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the meaning of denotation, connotation, and myths built through visual and verbal elements in the film *Di Kampuang Raso Marantau* by Ibel Santano, using Roland Barthes' semiotic approach. The research uses a qualitative method with a content analysis approach. The object of the study consists of 14 scenes that contain visual and verbal signs. Data collection was done through observation, documentation, and data inventory, and then analyzed based on denotation, connotation, and myth meanings. The research shows that at the denotative level, the film represents family conflicts, social exclusion, and the violence experienced by the character Adam. At the connotative level, the film depicts the struggle to gain social recognition, character education within the family, and the process of maturing. At the myth level, the film represents Minangkabau cultural values, especially the tradition of going abroad for work, honor, independence, and parental authority. Thus, this film not only serves as a form of entertainment but also as a medium for conveying moral, social messages, and preserving Minangkabau culture.